The Strategic Partners and Strategic Competitors between China and United States in the Period of Barack Obama Administration - Nur Arif Nugraha (Andalas Journal of International Studies (AJIS))
This essay will consider a number of perspectives to determine whether the relationship between China and United States is strategic partnersor strategic competitors. During the Obama administration, the policy toward China oscillates between being strategic partners and strategic competitors since the first time he became President in January 2009 until the present time.  In this essay, I will argue that the relationship between China and the United States should be based on partnership rather than competition considering the strategic position of both countries in the world recently, especially in terms of economic cooperation. However, there is still a sense of competition between them, especially in military sectors. Sometimes, the relationship between them in this sector often brings the tense to their relationship. Keywords: Obama administration, policy, strategic partners, strategic competitors, relationship.